Information computing and applications international conference, ICICA 2010, Tangshan, China, October 15-18, 2010, proceedings. Part I - Zhu, Rongbo (Springer eBooks., 2011)
This book constitutes the proceedings of the International Conference on Information Computing and Applications, held in Tangshan, China, in October 2010.